Genetic Identification in Early Onset Parkinsonism among Norwegian Patients. Issue 4 (23rd May 2017) - Gustavsson, Emil K.; Trinh, Joanne; McKenzie, Marna; Bortnick, Stephanie; Petersen, Maria Skaalum; Farrer, Matthew J.; Aasly, Jan O.
Abstract: Background: An initial diagnosis of Parkinson's disease (PD) is challenging, especially in patients who have early onset and atypical disease. A genetic etiology for parkinsonism, when established, ends that diagnostic odyssey and may inform prognosis and therapy. The objective of this study was to elucidate the genetic etiology of parkinsonism in patients with early onset disease (age at onset <45 years). Methods: Whole‐exome sequencing, copy number variability, and short tandem repeat analyses were performed. The analyses were focused on genes previously implicated in parkinsonism and dystonia in patients with early onset parkinsonism. Genotype‐phenotype correlations were assessed using regression models. Results: The patient cohort was characterized by early onset, slowly progressive parkinsonism with a mean age at onset of 39.2 ± 5.0 years (n = 108). By 10 years of disease duration, the mean Hoehn & Yahr stage was 2.6 ± 0.8, the mean Unified Parkinson's Disease Rating Scale, part III (motor part) score was 24.9 ± 12.1 (n = 83), and 30 patients were cognitively impaired at the last examination (Montreal Cognitive Assessment score ≤ 26). Ten patients with typical early onset PD harbored homozygous or compound heterozygous mutations phosphatase and tensin homolog‐induced putative kinase 1 ( PINK1 ) (n = 4), parkin ( PRKN ) (n = 3), or the leucine‐rich repeat kinase 2 ( LRRK2 ) c.6055 G to A transition (n = 3). In addition, 5 patients with more atypical disease were compound heterozygotes for the glucocerebrosidase gene ( GBA ) (n = 3) 1 was heterozygous for solute carrier family 2, member 1 ( SLC2A1 ) and another carried a novel ataxin 2 ( ATXN2 ) exon 1 duplication. In most patients, the cumulative mutational burden did not appear to contribute to age at onset or progression Conclusion: In this clinical series, 15 patients (14%) carried mutations that were linked to monogenic parkinsonism. GBA carriers were most likely to suffer an earlier cognitive demise. Nevertheless, the etiology for most patients with early onset PD remains to be determined.